Enhancing Crop Yield and Adaptability through Sustainable Soil Management: Effective and Eco-Friendly Practices - Dimitrios Bilalis; Ioannis Roussis; Ioanna Kakabouki (Plants)
The rapid growth of the global population has led to the construction of new residential colonies on fertile agricultural lands, resulting in a significant decline in crop production areas [...]